(3QSGdI aj GdbQGAGJs
(3ChdgG (B:s
(3aGJMI GdcJGH GdQMje eGdc jhe GdOjf hdG jPcQ NdGa CUMGHg ai GdEOZGe dCfg bO JbOe ShQI GdHbQI ajgG CQHY hKeGfhf MQakG s
(3BNQgG (B:s
(3PcQfG Yf CHj YeQh hef ZjQ ENJdGa GdhGh eG jJGf hSHYhf MQakG CeG jG bhe eGdi hCNhGJgG Qhi Hg OhM GHf hQYf CHj YeQh hJQc GdEOZGe JeJ HMeO Gddg hYhfg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(190) s
Keywords: (3GdeLGejYs